Successful Rescue of Massive Hemoptysis Caused by Vascular‐Bronchial Fistula - Xiangwu Zhang; Rongxian Zhou; Guangqiang Zhao; Wanling Chen; Yunchao Huang; Lianhua Ye (The Clinical Respiratory Journal)
ABSTRACT The case reported in this paper is a vascular‐bronchial fistula associated with fatal massive hemoptysis. The patient was rescued successfully by experts from a multidisciplinary team. The bronchoscopy physician cleared the accumulated blood in the airway timely and maintained the airway patency, and the anesthesiologist established artificial ventilation quickly; eventually, the thoracic surgeon performed an emergency thoracotomy to control the bleeding. It reflected the significance of multidisciplinary collaborative treatment.